(DIS) GENDER EQUALITY IN CORPORATE MANAGEMENT POSITIONS: WHAT HAS BEEN DONE FOR EQUAL OPPORTUNITIES? - de Oliveira Castro, Manoela; Mendes de Souza, Mariana; Karoline Gomes Lozi, Nicole (Revista Gênero e Interdisciplinaridade, 2022)
Gender inequality is present in various social spheres, especially in positions of power, such as corporate management. On the boards of directors of companies, for example, men are in the majority, compared to women. Similarly, inequality is present before the acquisition of a job, in the dispute in the labor market, even after professional conquests, since it is a popular preconception that women, especially when mothers, should not work, and, if working, they should not be allowed to work. leadership positions, tending to remain in the same “inferior” positions, or to a slower and smaller professional rise. In view of this, measures are needed that seek to change the scenario, internationally, if the millennium goals are observed, nationally, the creation of laws that impose equal entry into careers and, politically, the guarantee of exclusive vacancies for women. Furthermore, in the private sphere, in addition to legal provisions, there are also internal policies aimed at reducing the disparity between genders. In this scenario, the positioning of companies in this sense has been fundamental, strengthening the search for equality, making it more effective, permanent and stable.